Cost-effective transition metal based catalysts for low-temperature formaldehyde oxidation - Yusuf, Abubakakar (2020)
Formaldehyde (HCHO) is one of the most common indoor air pollutants which causes adverse health effects, and a known carcinogen which has been proven to cause nasopharyngeal cancer and leukaemia, over prolonged exposure. Catalytic oxidation, amongst the known techniques for HCHO removal, is the most promising, as it is capable of completely mineralizing HCHO into CO2 and H2O. Although noble metal-based catalysts are very active for HCHO oxidation, their practical application is limited by cost and availability. Transition metal-based catalyst offers a promising cost-effective alternative. However, improving their catalytic performance is critical to enhancing their competitiveness for practical and industrial application in indoor HCHO abatement. Birnessite-type manganese oxide (δ-MnO2) is a promising transition metal catalyst for HCHO removal from the indoor environment. Nonetheless, not much has been reported in the enhancement of its catalytic activity. This research focused on developing novel strategies to enhance the catalytic activity of δ-MnO2 through surface defect engineering using doping technique; the use of oxygen carrier; and fine-tuning the concentration of the cations present in its interlayer spaces. The developed catalysts were characterized and evaluated for HCHO oxidation. The surface reaction mechanism of HCHO oxidation was investigated via in situ Diffuse Reflectance Infrared Fourier Transform (DRIFTS). Defect engineering through the creation of oxygen vacancies has been demonstrated to be an effective strategy for enhancing the catalytic activity of δ-MnO2 for HCHO. Modification of δ-MnO2 using Co and Cu via metallic doping revealed that doping technique is promising in enhancing the catalytic activity of δ-MnO2. However, catalytic and characterization results revealed that not all dopants enhance catalytic activity. While Co showed a synergistic effect, an inhibition effect was observed in the presence of Cu. The incorporation of Co3+ into the lattice structure of δ-MnO2 enhanced the substitution of Mn4+, generation of oxygen vacancies and lattice defects, which promoted the formation of surface-active oxygen species, and enhanced catalytic activity for low-temperature oxidation of HCHO. Catalytic results showed that Co-doped δ-MnO2 completely mineralize HCHO (~170ppm, 120,000 ml∙g-1∙h-1) at 80°C compared to 90°C for the pristine δ-MnO2. Co-doped δ-MnO2 proved very active even under a very high space velocity of 400,000 ml∙g-1∙h-1. Its activity was further displayed in its ability to achieve room temperature oxidation of HCHO, averaging up to 93.5% conversion of ~10 ppm HCHO (60,000 ml∙g-1∙∙h-1) over 72 hrs of operation. However, dopant-intermediates interaction can adversely affect the activity of the modified catalyst. Cu doping on the other hand led to a drastic inhibition of catalytic activity, despite the relative increase in the surface oxygen vacancies and concentration of surface active oxygen, compared to the pristine δ-MnO2. In the presence of Cu, the catalytic activity of δ-MnO2 was inhibited, and the inhibitory effect increases with increasing Cu doping. DRIFTS analysis revealed that in the presence of Cu, carbonate intermediate species accumulate on the surface of the catalysts leading to the restricted access to catalyst’s active sites and reduced catalytic activity. CeO2 was used to further enhance the catalytic activity of Co-doped δ-MnO2. As an oxygen carrier, the oxygen storage capacity of CeO2 and its ability to transfer its lattice oxygen, was utilized to achieve a bimetallic co-doping of Co and Ce into δ-MnO2. Bimetallic doping of Co and Ce (0.05 = x/Mn; x: Co, Ce) did not show any significant enhancement in the activity of δ-MnO2, compared to the monometallic doped catalysts – Co-δ-MnO2 and Ce-δ-MnO2, with similar doping ratio. Both the bimetallic doped (0.05Co-0.05Ce) and monometallic doped catalysts (0.05Co-MnO2 and 0.05Ce-MnO2) showed similar activity trend and achieved complete oxidation of HCHO at 80°C (~170ppm, , 120,000 ml.g-1.h-1). Complete oxidation shifts to higher reaction temperature of 90 and 100°C for 0.05Co-0.2Ce and 0.05Co-0.5Ce, respectively. As the amount of CeO2 loading increases from 0.05 to 0.5 (Ce/Mn ratio), significant loss in the interlayer K+ and decrease in catalytic activity was observed due to surface accumulation of CeO2 and structural collapse of δ-MnO2. In addition, comparatively lower content of active oxygen species was observed at high CeO2 loading. Besides, methanol was detected over all the CeO2 containing catalysts except 0.05Co-0.05Ce. However, in the absence of Co, even at low doping ratio of 0.05 of CeO2 (0.05Ce-MnO2) methanol was detected. Methanol selectivity increases with increasing CeO2 content. DRIFTS analysis shows that methoxy specie, which is a methanol intermediate, is generated in the presence of CeO2. As such, the presence of CeO2 in the catalyst matrices leads to the generation of a secondary pollutant. This work raises questions on the health safety of using CeO2 as a catalytic material for the abatement of indoor air pollutant. The interlayer space of δ-MnO2 is composed of ions, mostly K+ or Na+, and water molecules which help in stabilizing the layered structure of δ-MnO2. In Chapter 5, the role of K+ in lattice oxygen mobility of manganese oxide catalysts for enhanced catalytic oxidation of formaldehyde (HCHO) was investigated. Manganese oxide catalysts with varying K+ content and tuneable concentration of lattice oxygen and Mn4+ were synthesized and investigated for HCHO oxidation. Acid treatment of the pristine catalysts led to the creation of oxygen vacancies, reduction in the surface concentration of lattice oxygen, Mn4+ and K+, and a resultant increase in surface area. Characterization results showed that high content Mn4+ enhances the redox properties of the catalyst and K+ improves the mobility and activity of the lattice oxygen to re-oxidize the reduced Mn active sites and provide more surface oxygen for HCHO oxidation. Catalytic activity increases with increasing K+ content, and the surface concentration of lattice oxygen and Mn4+. The catalyst with the highest amount of K+, lattice oxygen, and Mn4+ displayed the best catalytic activity, achieving complete HCHO conversion (170 ppm, 45% relative humidity (RH), 60,000 ml·g-1·h-1) at 70°C, and an average of 68% HCHO conversion (10 ppm, 60,000 ml·g-1·h-1, 45% RH) at room temperature for 72 hrs. Lattice oxygen test, in the absence of molecular oxygen, revealed that the lattice oxygen is involved in HCHO oxidation and K+ enhances its mobility. Acid treatment increases the concentration of surface adsorbed oxygen leading to an initial improvement in catalytic activity, but the absence of K+ impacted the mobility of the lattice oxygen and the activation of molecular oxygen to supplement the consumed oxygen species, resulting into reduced catalytic activity.